2012
DOI: 10.3329/bjsir.v47i2.11461
|View full text |Cite
|
Sign up to set email alerts
|

Loss of vitamin A in fortified edible oils and ghee during cooking in asian traditional style

Abstract: Vitamin 'A' is essential for normal growth and its deficiency causes night blindness, affects the regulatory function of skin and reduces the general resistance of organism to infection. This deficiency does not occur by using balanced diet or by fortification of staple food with appropriate amount of Vitamin 'A'. In Pakistan vitamin 'A' fortification is done in vegetable ghee/cooking oil. It is generally assumed that fortified amount of vitamin 'A' is fully destroyed when the food is cooked at high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…However, in the case of fried chili, vitamin A could not be detected, possibly due to its fat soluble nature. Vitamin A might have leached out of the green chili into the frying medium (oil), thus was not detected in fried chilies (Akhtar et al, 2012 ). Several other authors have also confirmed the degradation of vitamin A at a temperature range of 130–140°C (Chen et al, 1995 ; Oke et al, 2018 ) and complete loss in frying (Omotosho, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of fried chili, vitamin A could not be detected, possibly due to its fat soluble nature. Vitamin A might have leached out of the green chili into the frying medium (oil), thus was not detected in fried chilies (Akhtar et al, 2012 ). Several other authors have also confirmed the degradation of vitamin A at a temperature range of 130–140°C (Chen et al, 1995 ; Oke et al, 2018 ) and complete loss in frying (Omotosho, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Salah satu strategi untuk mengat asi fenomena ini adalah dengan fortifikasi vitamin A ke dalam bahan pangan. Fortifikasi miny ak dengan vitamin A telah dicanangkan dan dilakukan di berbagai negara seperti Thailand (Puysuwan et al, 2007), Nigeria (Oni, 2012), Pakistan (Akhtar et al, 2012), Uganda (Fiedler dan Afidra, 2010), dan Indonesia (A ndarwulan et al, 2014).…”
Section: Pendahuluanunclassified
“…Sayangnya Akhtar et al (2012) menemukan bahwa proses pemasakan dapat berakibat pada hilangnya kandungan vitamin A dalam minyak terfortifikasi. Jumlah vit amin A yang hilang terkait dengan makin tingginya suhu yang digunak an dan lamanya proses pemasak an.…”
Section: Pendahuluanunclassified